Relationship between innate immune response toll-like receptor 4 (Tlr-4) and the pathophysiological process of obesity cardiomyopathy - Rizzi Alves, Pedro Henrique [UNESP]; Togneri Ferron, Artur Junio [UNESP]; Costa, Mariane Róvero [UNESP]; Hasimoto, Fabiana Kurokawa [UNESP]; Gregolin, Cristina Schmitt [UNESP]; Garcia, Jéssica Leite [UNESP]; De Campos, Dijon Henrique Salomé [UNESP]; Cicogna, Antônio Carlos [UNESP]; De Mattei, Letícia [UNESP]; Moreto, Fernando [UNESP]; Zanati Bazan, Silméia Garcia [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; et al. (Sociedade Brasileira de Cardiologia, 2021)
Background: Obesity is a chronic low-grade inflammation condition related to cardiac disorders. However, the mechanism responsible for obesity-related cardiac inflammation is unclear. The toll-like receptor 4 (TLR-4) belongs to a receptor of the transmembrane family responsible for the immune response whose activation stimulates the production of proinflammatory cytokines. Objective: To test whether the activation of the TLR-4 receptor participates in the obesity cardiomyopathy process, due to cytokine production through NF-ĸB activation. Methods: Male Wistar rats were randomized into two groups: The control group (C, n= 8 animals) that received standard diet/water and the obese group (OB, n= 8 animals) that were fed a high sugar-fat diet and water plus 25% of sucrose for 30 weeks. Nutritional analysis: Body weight, adiposity index, food, water, and caloric intake. Obesity-related disorders analysis: Plasma glucose, uric acid and triglycerides, HOMA-IR, systolic blood pressure, TNF-α in adipose tissue. Cardiac analysis included: TLR-4 and NF-ĸB protein expression, TNF-α and IL-6 levels. Comparison by unpaired Student’s t-test or Mann- Whitney test with a p-value < 0.05 as statistically significant. Results: The OB group showed obesity, high glucose, triglycerides, uric acid, HOMA, systolic blood pressure, and TNF-α in adipose tissue. OB group presented cardiac remodeling and diastolic dysfunction. TLR-4 and NF-ĸB expression and cytokine levels were higher in OB. Conclusion: Our findings conclude that, in an obesogenic condition, the inflammation derived from cardiac TLR-4 activation can be a mechanism able to lead to remodeling and cardiac dysfunction.
Keywords: Adipocytes; Cardiovascular Diseases/physiopathology; Cytokines; Fatty Acid synthases; Inflammation; Nutrional Assessment; Obesity